Atlas - country resources for neurological disorders 2004 : results of a collaborative study of the World Health Organization and the World Federation of Neurology (WHO, 2004)
The main objectives were to obtain the expert information on the most common neurological conditions and their distribution in primary care and specialist settings; availability of neurological procedures, treatments and services; number and types of health professionals involved in the delivery of neurological care; characteristics of postgraduate teaching in neurology; budget for and financing of neurological care, including the types of health insurance and disability benefits; and availability role and involvement of national neurological associations and other nongovernmental organizations in advocacy to raise public and professional awareness of neurological disorders and their participation in the treatment rehabilitation and prevention of neurological disorders. The report organized by 15 broad themes based on above objectives is fully illustrated with maps, charts and graphs, and provides global and regional analyses of the neurological resources data. The results obtained from the study confirm that the available resources for neurological service in most countries of the world are insufficient compared with the global need for neurological care. The Neurology Atlas presents the facts and figures and highlights the large inequalities across regions and countries with low-income countries having extremely meagre resources. The information presented in this volume will be useful for a large range of readers including policy-makers, health planners and specialists on international as well as national level. The data will be used in their advocacy efforts for more and better resources for neurological care.Neurological disorders constitute a large and increasing share of the global burden of disease. Very little is known, however, about the resources available within countries to meet this burden. In order to fill the information gap in the area of neurological disorders and services in 2001 WHO decided to expand the Atlas Project into the area of neurology and to conduct a study of Country Resources for Neurological Disorders. The Atlas on Country Resources for Neurological Disorders (Neurology Atlas) presents for the first time, the most comprehensive collection and compilation of information on neurological resources across 109 countries covering over 90% of the world population. The World Federation of Neurology (WFN) collaborated closely in the collection and analysis of the data and the development of the Neurology Atlas, with the active participation of leading experts in neurology all over the world and valuable assistance from WHO regional advisers and WHO country representatives.
Keywords: neurovědy; World Health Organization; zdravotničtí pracovníci; Neurology; zdravotnické zdroje; veřejné zdravotnictví; Nervous System Diseases; Health Resources; Health Workforce; neurologie; Světová zdravotnická organizace; nemoci nervového systému